State-owned enterprises, state capitalism and social distribution in Singapore. Issue 4 (7th August 2016) - Huat, Chua Beng
Abstract: State-owned enterprises and sovereign wealth funds have 'insured' Singapore's domestic economy against financial crisis and restructuring interventions from multilateral institutions, engendered elite cohesion and political stability, binding middle class employees to the political system. This essay analyses paths by which the Singapore government established state-owned enterprises and transformed them into global enterprises. It also examines how sovereign wealth funds contribute to government social expenditure without increasing taxes. Such redistribution through state capitalism resonates with the People's Action Partys social democratic origins, inviting comparisons with contemporary developments in Chinese state-capitalism.